Information privacy and the digital generation gap: An exploratory study. Issue 4 (1st October 2016) - Halperin, Ruth; Dror, Yuval
ABSTRACT: Over the past decade, the demise of privacy has been repeatedly pronounced by renowned technology executives such as Mark Zuckerberg, who have declared privacy to be passé and anachronistic—"so 20th century"—or the concern of old people . However, there has been relatively little research into privacy perception and behavior among different generations that may relate to how people navigate their private lives in online settings. Furthermore, recent research has revealed the ways in which privacy concerns of young Internet users are enacted, thus challenging overgeneralized claims of a clear-cut generation gap associated with online privacy. As information privacy problems are becoming thornier, unfounded statements voiced by stakeholders with vested interests should be put to one side. Instead, systematic research is needed to understand how privacy is perceived and managed by people of different age groups, and what measures can and should be taken to address current and future concerns of Internet users across generations. We explore these questions and account for the results using a representative sample from Israel.